The Effect of Ice Breaking Implementation on Mathematics Learning Outcomes of Class VIII at SMP Negeri 2 Samarinda - Sa'diah, Siti Halimatus; Berahman, Berahman; Untu, Zainuddin; Fendiyanto, Petrus (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
The atmosphere of mathematics learning during the day seems less enjoyable so students quickly feel bored, and sleepy, have difficulty concentrating, and students' mathematics learning outcomes are low. Apart from that, teachers rarely provide refreshments such as icebreakers during learning. Therefore, it is important to carry out this research to determine whether or not there is a positive influence of the application of ice breaking on mathematics learning outcomesin class VIII of SMP Negeri 2 Samarinda. This research uses a quasi-experimental method with a posttest-only control group design. The research population consisted of 339 class VIII students divided into 11 classes. The sample was taken deliberately, namely by selecting two classes that had a mathematics subject schedule from 13.00 to 15.00 WITA and the final grades for the odd semester were not significantly different. Data on mathematics learning outcomes was obtained through posttest. Then, descriptive and inferential statistics (t-test) were used to analyze the data that had been obtained. The results of the right-tailed hypothesis test show a probability value of 0.024 < 0.05 so H0 is rejected. So, there is a positive influence of the application of ice breaking on mathematics learning outcomes in class VIII of SMP Negeri 2 Samarinda.